A Case of Acute Prosthesis Migration after Femoral Head Replacement due to Osteomalacia by FGF23-Induced Tumor. (27th November 2012) - Hayashi, Shinya; Nishiyama, Takayuki; Fujishiro, Takaaki; Hashimoto, Shingo; Kanzaki, Noriyuki; Kawamoto, Teruya; Akisue, Toshihiro; Nishida, Kotaro; Kurosaka, Masahiro
Abstract : Fibroblast growth factor 23 (FGF23) was recently identified as an important factor involved in the development of hypophosphatemic rickets and osteomalacia. We experienced a rare case of acute prosthesis migration after hemihip arthroplasty due to FGF23-induced tumor. The patient underwent femoral head replacement because of femoral neck fracture, but prosthesis migration was occurred at 1 week after operation. The patient took various examinations, and FGF23-induced tumor was found in his right wrist. The tumor was resected, and he underwent total hip arthroplasty 8 month later. Finally, he was able to obtain free gait without pain.